Г.ЕСЕМУРАТОВА ГҮРРИҢЛЕРИНДЕ ДӘЎИР ШЫНЛЫҒЫНЫҢ СӘЎЛЕЛЕНИЎИ - Ктайбекова, Зулфия Кенгесбаевна (ILIM hám JÁMIYET, 2026)
The article analyzes the ideological and thematic directions of the stories of the famous writer G.Esemuratova, the heavy consequences of the war, and the tragic imprint they left on the fate of people. The objects of the study were the writer’s stories "Wounded Warrior", "Handkerchief Returned to its Owner", "Only Longing", "The Secret of the Teacher", "Dreamy Devil Cart", "Egg Flour and the Old Woman". The stories analyze the truth of the times, the heavy losses of the war in the fate of the people, and the heavy wounds it left in the hearts of people through examples.